Acorn‐Weevil Interactions in Semi‐Humid Evergreen Broad‐Leaved Forests in Yunnan, China: Trade‐Offs Among Acorn Functional Traits - Shengquan Fang; Chongyun Wang; Shaoji Hu; Mingchun Peng; Yongping Li; Chunyan Lan; Xinrong Li; Dengpeng Chen; Biao Zhao (Ecology and Evolution)
ABSTRACT Acorns are crucial for the regeneration and stability of oak forest communities, yet they often suffer significant predation by weevils before dispersal. Understanding the interaction between acorn functional traits and weevil infestation is essential for elucidating plant‐insect coevolution. This study examined the relationship between acorn functional traits and weevil infestation rates in six dominant Fagaceae species (Quercus schottkyana, Q. delavayi, Q. franchetii, Castanopsis delavayi, C. orthacantha and Lithocarpus dealbatus) in semi‐humid evergreen broad‐leaved forests in Yunnan, China. The results showed significant interspecific variation in acorn traits and infestation rates. L. dealbatus had the lowest infestation rate (9%), associated with its thick pericarp (0.88 mm), while Quercus species with higher levels of secondary metabolites (total phenols, flavonoids and tannins) exhibited higher infestation rates (34%–51%). Castanopsis species maintained moderate infestation rates with a combination of moderate physical defences and high starch content. Mixed‐effects models revealed that morphological and chemical traits together explained 38% of the variation in infestation rates, with pericarp thickness and tannin content being key inhibitory factors. Infested acorns upregulated secondary metabolite concentrations as a defensive response, reflecting phenotypic plasticity. Standardised major axis regression confirmed stable trade‐offs between physical and chemical defences, as well as between defence compounds and nutrient reserves. Even in the absence of weevil infestation, resource allocation strategies were inherent. We propose a three‐tier defence model: physical barriers (pericarp/cicatrix), chemical defences (total phenols/tannins) and nutrient regulation (starch reallocation). These complementary strategies collectively maintain forest community stability. The study provides new insights into plant–animal coevolution and supports conservation efforts for semi‐humid evergreen broad‐leaved forests.